Association of nevus count with prevention attitudes and behaviors before melanoma diagnosis. Issue 5 (October 2016) - Mayer, Jonathan E.; Swetter, Susan M.; Miller, Donald R.; Sober, Arthur J.; Johnson, Timothy M.; Geller, Alan C.
Abstract : Although melanoma risk factors are commonly known to healthcare professionals, the extent to which the at-risk public is either aware of these factors or perceives their risk accordingly has rarely been studied. We sought to investigate whether the presence of known melanoma risk factors, such as high total nevus and atypical nevus counts, was associated with increased prevention attitudes and behaviors, such as skin self-examinations and physician skin examinations. This was a retrospective study of 566 individuals recently diagnosed with melanoma in two large academic centers. Most prevention attitudes and behaviors did not vary on the basis of total nevi or atypical nevi counts. However, younger patients (<60 years) with many total nevi (>50) were more likely than those with fewer nevi (<20) to believe that they were at-risk for melanoma (42 vs. 23%; P <0.05), and more likely to state that they had been instructed on the signs of melanoma (36 vs. 21%; P <0.05). Patient and health provider recognition of the impact of nevus count on melanoma risk presents a unique and mostly untapped opportunity for earlier detection.